Self-instructional art modules for grade six pupils - Batilo, Concepcion Fermin 1937-
This research paper is concentrated on the development of "self-instructional art modules for Grade Six pupils". A questionnaire-survey instrument containing a list of all grade six art activities prescribed in the minimum learning continuum plus some supplementary activities was constructed and implemented. The activities included are: (1) Hand Puppet; (2) Finger Printing; (3) Linear Design; (4) Molding; (5) Papier Mache; (6) Weaving; (7) Spattering; (8) Printing; (9) Handicraft; and (10) Project from Discarded Materials.